Risk Factor for Poor Patient Satisfaction After Lumbar Spine Surgery in Elderly Patients Aged Over 80 years. Issue 4 (May 2021) - Hikata, Tomohiro; Ishii, Ken; Matsumoto, Morio; Kobayashi, Kazuyoshi; Imagama, Shiro; Ando, Kei; Ishiguro, Naoki; Yamashita, Masaomi; Seki, Shoji; Terai, Hidetomi; Suzuki, Akinobu; Tamai, Koji; et al.
Abstract : Study Design: Retrospective cohort study. Objective: To clarify the poor patient satisfaction after lumbar spinal surgery in elderly patients. Summary of Background Data: As the global population continues to age, it is important to consider the surgical outcome and patient satisfaction in the elderly. No studies have assessed patient satisfaction in elderly patients undergoing surgical treatment and risk factors for poor satisfaction in elderly patients after lumbar spinal surgery. Materials and Methods: A retrospective multicenter survey was performed in 169 patients aged above 80 years who underwent lumbar spinal surgery. Patients were followed up for at least 1 year after surgery. We assessed patient satisfaction from the results of surgery by using a newly developed patient questionnaire. Patients were assessed by demographic data, surgical procedures, complications, reoperation rate, pain improvement, and risk factors for poor patient satisfaction with surgery for lumbar spinal disease. Results: In total, 131 patients (77.5%, G-group) were satisfied and 38 patients (22.5%, P-group) were dissatisfied with surgery. The 2 groups did not differ significantly in baseline characteristics and surgical data. Postoperative visual analog scale score for low back pain and leg pain were significantly higher in the P-group than in the G-group (low back pain: G-group, 1.7±1.9 vs. P-group, 5.2±2.5, P <0.001; leg pain: G-group, 1.4±2.0 vs. P-group, 5.5±2.6, P <0.001). Multivariate regression analysis revealed that postoperative vertebral fracture ( P =0.049; odds ratio, 3.096; 95% confidence interval, 1.004–9.547) and reoperation ( P =0.025; odds ratio, 5.692; 95% confidence interval, 1.250–25.913) were significantly associated with the patient satisfaction after lumbar spinal surgery. Conclusions: Postoperative vertebral fracture and reoperation were found to be risk factors for poor patient satisfaction after lumbar spinal surgery in elderly patients, which suggests a need for careful treatment of osteoporosis in addition to careful determination of surgical indication and procedure in elderly patients. Level of Evidence: Level III.